Global sensitivity analysis of influence parameters in pitting corrosion behavior of 304 stainless steel using adaptive neuro‐fuzzy inference systems. Issue 5 (23rd November 2020) - Xu, Kaixin; Sun, Wen; Wang, Lida; Yang, Zhengqing; Wang, Jing; Wang, Suilin; Liu, Guichang
Abstract: Pitting corrosion is simultaneously influenced by many parameters. However, conventional experimental methods do not offer information on the relative importance of each parameter to pitting corrosion. Herein, pitting corrosion of 304SS under multiple parameter influences was investigated by the global sensitivity analysis (GSA) based on adaptive neuro‐fuzzy inference system (ANFIS). It was applied for the first time in quantitatively analyzing the relative importance of each parameter to pitting corrosion. It was developed in two different systems, based on the experimental data and the published data, respectively. Both results show that ANFIS exhibits a highly accurate prediction result. The GSA based on ANFIS quantitatively analyzes the relative importance of the initiation of pitting corrosion of 304SS for each parameter, and based on the results of GSA, it can also be determined whether the parameter inhibits or promotes pitting corrosion. We believe this method could provide guidance for corrosion research. Abstract : Pitting corrosion of 304SS under multiple parameter influences was investigated by the global sensitivity analysis (GSA) based on adaptive neuro‐fuzzy inference system (ANFIS) for the first time. It quantitatively analyzes the relative importance of the initiation of pitting corrosion of 304SS for each parameter, and based on the results of GSA, it can be determined whether the parameter inhibits or promotes pitting corrosion.